Therapeutic effect of aqueous extract from Ampelocissus africana (Lour) Merr rhizomes on testosterone-induced benign prostatic hyperplasia in Wistar rats - Wendkouni Leila Marie Esther Belem-Kabré; Ollo Da; Ernest Nogma Sombié; Raïnatou Boly; Geoffroy Gueswindé Ouédraogo; Windingoudi Rimwagna Christian Ouédraogo; Zakaline Yabré; Jean Noel Dado Koussé; Lazare Belemnaba; Assita Lamien-Sanou; Noufou Ouédraogo (Shahrekord University of Medical Sciences, 2024)
Introduction: Ampelocissus africana is a medicinal plant used to treat several diseases, including those affecting the prostate. This study investigated the effects of the aqueous extract of rhizomes from Ampelocissus africana (AAA) on a testosterone propionate (TP)-induced benign prostatic hyperplasia (BPH) model. Methods: The effect of the extract at 50, 150, and 300 mg/kg on BPH in male rats was assessed using daily subcutaneous injections of 3 mg/kg TP for four consecutive weeks. After the induction schedule, physical parameters, prostate index (PI), serum biochemical parameters, homogenate antioxidant, enzyme parameters, and prostates histopathological studies were carried out. Triterpenes and sterols were also assessed. Results: Treatment with AAA reduced the PI level in a dose-dependent manner (up to 75.91% at the dose of 300 mg/kg). The inflammatory marker measured in the present study, namely C-reactive protein, increased significantly in the BPH group and improved with the treatments. In addition, AAA reduced oxidative stress by decreasing the malondialdehyde (MDA) level and increasing the catalase (CAT) and superoxide dismutase (SOD) levels in comparison to the positive control group. A histopathological examination corroborated the result of the analysis of the physical and biochemical parameters. The study also showed interesting levels of triterpenes (119.5 ± 4.5 mg UAE/g) and sterols (104.6 ± 3.06 mg CE/g). Conclusion: These results suggest that the aqueous extract of Ampelocissus africana could be used as a natural herbal therapy to treat BPH.